A CORRELATIONAL–COMPARATIVE STUDY OF MOTIVATION AND PERCEIVED PARENTAL ENCOURAGEMENT FOR LEARNING CHINESE AS A FOREIGN LANGUAGE OF GRADES 5 AND 6 STUDENTS AT KHLONG TOEI WITTAYA SCHOOL, BANGKOK, THAILAND - WANG, YING; KARNJANAPUN, SUPIT (Scholar: Human Sciences, 2022)
The purpose of this study was to determine the relationship between Grades 5 and 6 students’ motivation and their perceptions of parental encouragement for learning Chinese as a foreign language and to compare two variables in grades 5 and 6 levels at Khlong Toei Wittaya School, Bangkok, Thailand. The participants of this study were 109 students from Grades 5 and 6 at Khlong Toei Wittaya School, Bangkok, Thailand. This study was designed as a quantitative correlational-comparative study. An adapted version of Gardner’s (2004) Attitude/Motivation Test Battery (AMTB) was used to collect data from 61 Grade 5 and 48 Grade 6 students during the 2019-2020 academic year. Descriptive statistics means standard deviations, correlational analysis (Pearson’s product-moment correlation coefficient), and an independent samples t-test (2-tailed) were used to analyze the data. The study found that Grades 5 and 6 students’ motivation for learning Chinese as a foreign language at Khlong Toei Wittaya School and their perceptions of parental encouragement for learning Chinese as a foreign language were slightly high. Also, a significant positive relationship between motivation and perception of parental encouragement for learning Chinese as a foreign language was found for each grade level. Furthermore, the findings also indicated no significant difference between Grades 5 and 6 students’ motivation for learning Chinese as a foreign language and no significant difference between their perceptions of parental encouragement for learning Chinese as a foreign language.